Comparison of Antidiabetic and Antioxidant Activities of Sweet and Bitter Apricot Kernels - Kaya , Gulsen; Keskin, Merve (Progress in Nutrition, 2021)
Fruits and their kernels have important phytochemical components for human health and nutrition. The fruits and their kernels have antioxidant effects by their seconder metabolites. Apricot (Prunus armeniaca L.) is an important fruit because of its functional properties with both its fruits and kernels. Therefore, in this study, total phenolic, flavonoid content, ferric reducing antioxidant power (FRAP) and inhibition properties of α-amylase enzyme of fruit, sweet and bitter apricot kernels were investigated. Methanol extract of each part of this fruit was prepared respectively. Total phenolic content as 241.83±1.47; 118.15 ± 2.03 and 60.41 ± 0.97 mg GAE/100 g, flavonoid content as 177.05±1.68; 20.08 ± 0.63 and 32.16 ± 0.51 mg QE / 100 g; antioxidant capacity as 0.81±0.02; 0.66 ± 0.01 and 0.27 ± 0.02 mM Fe2+/ mL extract were determined respectively. IC50 values for alpha amylase inhibition were calculated as 1.30±0.02; 0.74 ± 0.01 and 3.17 ± 0.01 mg/mL for fruit, sweet and bitter kernel extract respectively. The extracts showed good amylase inhibition properties. It can be concluded that apricot fruit and kernels might be used as a food supplement in Diabetes mellitus.